2022
DOI: 10.32539/jkk.v9i3.18828
|View full text |Cite
|
Sign up to set email alerts
|

Case Report : Low Level Immunoglobuling (Igg) in Reinfection Covid-19 Case

Abstract: Million people have infected the SARS-CoV-2 epidemic, which is currently spreading. We describe a confirmed COVID-19 patient whose oropharyngeal swab test for SARS-CoV-2 RNA and have positive PCR test results after 8 weeks proclaim negative result of PCR test for SARS-COV-2. ImmunoglobulinG was not detected during the initial illness. In this study, we discuss the potential role of low IgG in cases of reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…COVID-19 caused some clinical manifestation from asymptomatic, mild case, moderate case, severe pneumonia and critical case [8], [9]. Reinfection of COVID-19 was also happened in Bengkulu city [10].…”
Section: A Introductionmentioning
confidence: 95%
“…COVID-19 caused some clinical manifestation from asymptomatic, mild case, moderate case, severe pneumonia and critical case [8], [9]. Reinfection of COVID-19 was also happened in Bengkulu city [10].…”
Section: A Introductionmentioning
confidence: 95%
“…The previous study showed that each patient exhibited varying IgG antibody levels, and patients with mild, moderate, and severe clinical manifestations showed a different trend, respectively [8]. Then, reinfection of SARS-Cov-2 could affect lower IgG levels [9].…”
Section: Introductionmentioning
confidence: 97%